Self‐Assembly of A Novel Ag48 Cluster Encapsulating an Unprecedented [Mo8O28]8− Anion Template. Issue 3 (7th December 2018) - Wang, Zhi; Zhuo, Hong‐Yan; Hu, An‐Yi; Su, Hai‐Feng; Zhao, Quan‐Qin; Wang, Xing‐Po; Tung, Chen‐Ho; Sun, Di
Abstract: A novel silver cluster (SD/Ag48a ) co‐protected by p ‐MePhS − and CF3 COO − ligands with an in‐situ generated unprecedented [Mo8 O28 ] 8− template has been synthesized under solvothermal condition. Single‐crystal X‐ray diffraction (SCXRD) and electrospray mass spectrometry (ESI‐MS) were used to determine the atom‐precise structure and solution behavior, respectively. Interestingly, the rare [Mo8 O28 ] 8− ion observed in the center ofSD/Ag48a consists of 8 edge‐shared MoO6 octahedra or can be deemed as three Mo4 O4 cubes fused together by sharing faces. The UV‐Vis spetcrum exhibits that a high‐energy (HE) wide absorption centered at ca. 365 nm, which can be assinged to intraligand (IL) π→π* transition absorption, whereas the low‐energy (LE) shoulder peak centered at ca. 500 nm can be ascribed to ligand‐to‐metal‐charge‐transfer (LMCT, S 3p→Ag 5 s) transition. Abstract :